Economic Community of West African States at forty-five: a fool at forty-five a fool forever? - Nwosumba, Victor (African Journal of Politics and Administrative Studies, 2020)
Amid COVID-19 pandemic lockdown in the year 2020, Economic Community of West African States hereafter called ECOWAS quietly celebrated its forty-five years of establishment. Widely, much was not heard of or written about the community probably due to the challenges of the pandemic. However, the address of the President of ECOWAS Commission to the staff of ECOWAS institutions on the occasion of the commemoration of the community’s forty-fifth anniversary serves as a reminder that attention should also be given to this regional giant against all odds. Thus, the purpose of this paper is to celebrate ECOWAS at forty-five and then examine whether it is a fool at forty that is proverbially referred to as a fool forever. The paper, through thorough examination of the data collected from secondary sources finds that ECOWAS is still far from achieving its main mandate, its achievements as orchestrated by His Excellency, the President notwithstanding. The paper argues that the postponement of the establishment of ECO, a common currency for the region for the sixth time from 2020 to yet to be announced date, lack of realistic free movement of persons and goods among members and selfish interests of its leaders in the guise of national interest are enough reasons to conceive ECOWAS as a fool at forty-five. With the aid of constructivist theory,it concludes that even if ECOWAS at forty-five is still fooling around it has the chances of not being a fool forever if the leaders should turn a new leaf and pursue the attainment of the community’s mandate before its fiftieth anniversary.

The Effectiveness of the Harmonization Tool Adopted Under the Ohada Regime - Ceesay, Buba (Social Science Research Network, 2020)
The Organization for the Harmonization of Business Law in Africa, OHADA, is a regional entity whose primary objective is to harmonize the Business Law of its members. It has adopted legislative measures and institutional setups to ensure the realization of this object. This paper critically examined the effectiveness of the harmonization tool adopted under OHADA. The paper first gives a brief overview of OHADA setups, then the advantages and shortcomings of the harmonization tool adopted under the OHADA regime and finally concluded that though OHADA is a major step towards the attainment of harmonization of business law and Integration with the view of fostering development and business activities, its harmonization tool is lacking full efficacy towards the attainment of the objectives of the organization due to prevailing limitations and challenges.
Keywords: SSRN

The OHADA Structure as a Possible Model for the Development of a Commercial Law Structure in the Southern African Development Community (SADC) - Leno, Ngaundje Doris (International Journal of Social Sciences and Management Review, 2020)
The Southern African Development Community's (SADC) colonial legacy which introduced foreign legal traditions and the consequences of the diversity heighten the urgency for unified commercial legislation to deal with cross-border disputes.Thus, the issue is whether the Organisation for the Harmonisation of Business Law in Africa (OHADA) structure can serve as a possible model for the development of a uniform commercial law structure in the SADC .Despite the success of the OHADA, the author submits that the OHADA can only serve as a source of inspiration, or roadmap, providing guidance to the SADC drafters.The paper aims at demonstrating that the OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC.The significance of this paper lies in the contributions it makes to the development of a commercial law structure in the SADC.
Keywords: Development; Integration; Model; OHADA; SADC

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Keywords: Africa Union; Algeria; Intégration régionale

The role of the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) in facilitating continental integration - Luthuli, Isaac (University of KwaZulu-Natal, 2020)
The dissertation examines the role the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) can play in facilitating the political and economic convergence of the African Union (AU) member states. The developmental challenges facing Africa in spite of its wealth of human and natural resources is poignant. The genesis of this problem can be traced to the history of colonialism and the wave of independence in the continent in the late 1950s. Arguments have been put forward to suggest that one of the most viable ways of promoting Africa’s development is by developing and promoting intra-continental trade which can be possible through continental integration. The specific areas reviewed are regional stability and how intra-regional trade and investment is used to promote economic convergence. Africa's need for political and economic integration at a continental level is further sustained by the assumption that neocolonialism can be blamed for the weakness of structures in African states. Some scholars agree on the idea that regionalisation is often seen to offer a possibility to respond to the challenges of globalization. This impact nevertheless is dependent on the relation between globalisation and regional sentiment. Regional integration implies a form of interdependence among nation-states. Such interdependence leads to an establishment of regional integration arrangements between sovereign states within a geographical space. These agreements are shaped formally and there is a commitment to work together in order to realise political and socio-economic benefits. This study maintains that in order to achieve effective integration of the continent, Nigeria and South Africa as case studies, as continental giants have a key role to play to this end and as members of ECOWAS and SADC respectively. It is argued here that both the SADC and ECOWAS as sub-continental blocks have made some notable and commendable progress in developing policies for trade liberalization and economic integration, this, however, is not enough as such policies are also pertinent at a continental level. The study found that SADC and ECOWAS as regional blocks can play a role in aiding the continent to achieve a trade liberalization to achieve continental economic development.
Keywords: African integration; ECOWAS; Economic Development; Economic convergence; Integration; Intra-continental trade; SADC